Deaths in Immigration and Customs Enforcement (ICE) Detention, 2011–2018. Results of an Analysis of 55 Detainee Death Reviews. (15th September 2021) - Grassini, Molly; Terp, Sophie; Fischer, Briah; Ahmed, Sameer; Ross, Madeline; Frenzen, Niels; Kearl, Naomi; Burner, Elizabeth; Parmar, Parveen
Abstract : Research Objective: Since 2017, intensified deportation efforts against immigrants have increased the population in Immigration and Customs Enforcement (ICE) detention nationally. ICE assumes responsibility for the health and safety of individuals in their custody for the duration of detention, as mandated by their Performance‐Based National Detention Standards (PBNDS). Following the death of an individual in detention, the ICE Office of Detention Oversight produces Detainee Death Reviews (DDR). DDRs evaluate circumstances surrounding the death and determine whether PBNDS were violated. To gain a more comprehensive understanding of ways in which health systems factors may have contributed to deaths in ICE detention facilities, we systematically analyzed the text of 55 DDRs conducted between 2011 and 2018. Study Design: A total of 55 DDRs from 2011 to 2018 were obtained via a combination of the Official Department of Homeland Security ICE Freedom of Information Act website and from civil rights organizations. Data was extracted from each DDR using a standardized tool. Data extracted described the deceased's demographic information, immigration, criminal, and medical histories, objective medical data, and any PBNDS violations identified and acknowledged in each death report. Population Studied: Individuals who died while in ICE detention. Principal Findings: The research team successfully obtained DDRs for 55 (92%) of 69 reported deaths 5–7 among individuals in ICE detention between 2011 and 2018. Individuals who died were predominantly male (86%); averaging 42.7 years of age at the time of death. The deceased had lived in the United States for a mean of 15.8 years prior to entering ICE detention and spent a median of 39 days (range 1–1865; mean 120) in ICE custody prior to death. Individuals who died had relatively low burdens of pre‐existing disease as illuminated by Charlson Comorbidity Index (CCI) scores of 0 (33%) or 1–2 (27%). Markedly abnormal vital signs were documented prior to 51% (28) of deaths, with 71% (20) of deaths preceded by abnormal vital signs during multiple encounters prior to death or hospital transfer . Most deaths (n = 47, 85%) were attributed to medical causes, while 8 (15%) were attributed to suicide. None of the individuals who committed suicide were on suicide watch at the time of death; though half had been at some time during their detention. Among 55 death summaries, a total of 86 counts of PBNDS deficiencies were noted across 7 categories. Overall, 43 (78%) of DDRs identified PBNDS deficiencies related to Medical Care, with a mean of 3.16 deficiencies related to Medical Care per case (Range 1–13). Conclusions: Findings suggest that substandard medical care occurring within ICE detention facilities may have contributed to or failed to prevent deaths of multiple individuals in ICE detention between 2011 and 2018. Additionally, the detention death review process found the majority of detention facilities had violated ICE's own medical standards repeatedly. Implications for Policy or Practice: These results highlight the need for further independent investigations into medical and psychiatric care provided to individuals in ICE detention facilities, and greater mechanisms for external accountability. Primary Funding Source: Haas JR Foundation.